Penetration into Host Cells of Naked, Partially Injected (Post-FST) DNA of Bacteriophage T5 - Labedan, B. (J Virol, 1973)
The experiments presented here suggest that the naked post-FST DNA, attached to the bacteria after a centrifugation at 6,000 × g of Escherichia coli-T5 complexes arrested at the FST stage, can be injected into the host cell if protein synthesis is allowed. This results from the observation that the production of infectious centers by this naked DNA is sensitive to DNase or moderate shearing treatments. The process of injection seems to be the same as that for DNA normally rolled in an adsorbed capsid.